Colletotrichum species causing anthracnose disease on avocado fruit in Taiwan - Wu, C. J.; Lin, M. C.; Ni, H. F.
Anthracnose disease caused by Colletotrichum spp. is a limiting factor in avocado production worldwide. In Taiwan, Colletotrichum spp. cause post-harvest disease on avocado and greatly reduce the shelf life of the fruit. The aim of this study was to identify the species causing avocado anthracnose in Taiwan and characterize their pathogenicity. In this study, mature avocado fruits with brown lesions were collected from 13 orchards in avocado production areas in Taiwan from 2008 to 2010 and from 2019 to 2020. Eighty-seven Colletotrichum isolates were isolated from the lesions of avocado fruits. Eighty-six isolates were assigned to the Colletotrichum gloeosporioides species complex according to the Apn2-Mat1-2 intergenic spacer and partial mating type (Mat1-2)gene (ApMat)sequence. A preliminary phylogenetic analysis based on ApMat sequences indicated that the 86 isolates formed four clades, C1 to C4. A multi-gene phylogeny based on partial actin, calmodulin, chitin synthase (CHS), GAPDH, ribosomal internal transcribed spacer, and beta-tubulin (TUB)sequences further confirmed the species in the four clades, namely Colletotrichum fructicola (C1), Colletotrichum siamense (C2 and C4), and Colletotrichum tropicale (C3). One isolate, Col-735, was identified to be Colletotrichum eriobotryae according to a phylogenetic tree constructed with the CHS, GAPDH, and TUB sequences. Pathogenicity tests on wounded 'Choquette' and 'Zhongpu green peel' avocado fruits showed the above four Colletotrichum species were pathogenic on these fruits. This is the first report studying Colletotrichum species and their pathogenicity on avocado in Taiwan, and C. eriobotryae is reported as an avocado fruit pathogen for the first time.
Keywords: COLLETOTRICHUM SPP; MULTI-LOCUS SEQUENCE ANALYSIS; AVOCADO; PATHOGENICITY TEST